2018
DOI: 10.3389/fmicb.2018.03065
|View full text |Cite
|
Sign up to set email alerts
|

Small-Scale Soil Microbial Community Heterogeneity Linked to Landform Historical Events on King George Island, Maritime Antarctica

Abstract: Although research on microbial biogeography has made great progress in the past decade, distributions of terrestrial microbial communities in extreme environments such as Antarctica are not well understood. In addition, knowledge of whether and how historical contingencies affect microbial distributions at small spatial scales is lacking. Here, we analyzed soil-borne microbial (bacterial, archaeal, and fungal) communities in 12 quadrat plots around the Fildes Region of King George Island, maritime Antarctica, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 90 publications
2
8
0
Order By: Relevance
“…According to the PCA analysis ( Figure S2), TR1 diverges from the other samples by being related with higher concentrations of Hg, Pb, Zn, and Cd in soils, thus these chemical variables may be driving differences in the taxonomic composition of this sample. The bacterial community distribution, including the most abundant bacterial phyla (Proteobacteria, Bacteroidetes, Acidobacteria, and Actinobacteria) are in agreement with previous reports in Fildes Peninsula [20,23].…”
Section: Diversity Of 16s Rrna Gene Ks and Ad Domains In The Maxwellsupporting
confidence: 92%
See 2 more Smart Citations
“…According to the PCA analysis ( Figure S2), TR1 diverges from the other samples by being related with higher concentrations of Hg, Pb, Zn, and Cd in soils, thus these chemical variables may be driving differences in the taxonomic composition of this sample. The bacterial community distribution, including the most abundant bacterial phyla (Proteobacteria, Bacteroidetes, Acidobacteria, and Actinobacteria) are in agreement with previous reports in Fildes Peninsula [20,23].…”
Section: Diversity Of 16s Rrna Gene Ks and Ad Domains In The Maxwellsupporting
confidence: 92%
“…In Antarctic soils, the percentage of yet-uncultured genera is expected to be much higher [14] than the 82% described for general soils [15]. A considerable fraction of such uncultured bacteria corresponds to members of the NP-rich Actinobacteria [16,17] and Cyanobacteria [18,19] phyla.King George Island is one of the largest ice-free and biodiverse areas in maritime Antarctica [20]. It harbors a high density of scientific stations, particularly in Maxwell Bay [21], where most of terrestrial biology research takes place.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous research on the soil microbial community in Fildes Peninsula, Antarctica, we found that the microbial community in this area was affected by geological events. The microorganisms in the coastal uplifted chronosequence were significantly different from those in other areas and were still in an unstable change stage ( Zhang et al, 2018 ). In this area, the coastal uplifted chronosequence of Ardley Island terrace presents a very complete six-spatial strata.…”
Section: Introductionmentioning
confidence: 99%
“…Spatial heterogeneity driven by environmental conditions guarantees substantial redundancies in soil microbial functions ( Shi et al, 2021 ). On small spatial scales, microbial distribution patterns are a legacy of historical events, such as geological evolutionary processes ( Zhang et al, 2018 ). Microbial studies of grazing systems, compared with agricultural systems, are relatively limited, particularly in woody rangeland ecosystems ( Kooch et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%